Acupuncture as a Therapeutic Intervention for Alleviating Pain Associated with Knee Osteoarthritis in the Elderly - Ida Ayu Suptika Strisanti; Ida Ayu Anom Rastiti; Kadek Buja Harditya; I Dewa Ayu Agra Darmawati; Komang Rosa Tri Anggaraeni (Babali Nursing Research)
Introduction: Osteoarthritis is a common joint disease associated with aging, with knee osteoarthritis (KOA) affecting both elderly men and women in Indonesia. KOA is a major cause of disability and immobility, significantly impacting the quality of life of the elderly. Acupuncture is frequently used as a complementary and alternative medicine therapy to alleviate pain associated with KOA. This study aims to investigate the effect of acupuncture in relieving KOA-related pain in the elderly.